USAGE OF PODCASTS IN DEVELOPING LISTENING AND SPEAKING SKILLS OF ENGLISH LANGUAGE LEARNERS - Allabergenova Shoira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This research explores the pedagogical efficacy of podcasts in enhancing students’ English language proficiency, specifically focusing on listening and speaking skills. Within the contemporary landscape of educational technology commonly referred to as EdTech, podcasts represent a compelling example of interactive media leveraged to facilitate classroom learning. Building upon a critical review of existing literature, this study develops and implements a pedagogical framework integrating podcast utilization. The findings reveal a transformative impact of technology integration on both students and instructors. Students demonstrate significantly increased engagement and motivation, actively pursuing the enhancement of their listening and speaking skills through technologically mediated learning experiences. The enriched learning environment, facilitated by the diverse content and interactive nature of podcasts, foster a marked improvement in their linguistic capabilities. Concurrently, the study highlights the pedagogical imperative for educators to develop a robust capacity for integrating technological tools, such as podcasts, into their teaching practices, thereby fostering a more dynamic and engaging learning environment. The vast and diverse thematic resources offered by podcasts provided a wealth of opportunities for both students and teachers to expand their knowledge base and refine their skills within a formally structured educational context.